2023
DOI: 10.3390/metabo13090982
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Phenylalanine Metabolism of Procapra przewalskii in Chronic Selenosis in Selenium-Enriched Habitats

Hong Ren,
Ping Zhou,
Xiaoyun Shen

Abstract: Selenium (Se)-enriched habitats have led to chronic selenosis, seriously affecting the health and survival of Procapra przewalskii (P. przewalskii). Our targets were to explore the molecular mechanisms of chronic selenosis and to look for a new way to protect endangered species. The mineral contents of soils, grass, blood, and muscle were analyzed. The biochemical indices, antioxidant capability, and immune function were also investigated. The analyses of proteomics and metabolomics were also carried out. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Research in both animals and humans has demonstrated a significant correlation between Cu deprivation and anemia. Cu plays a crucial role in the body, particularly in the formation of red blood cells, as it is a cofactor for enzymes involved in hemoglobin synthesis and Fe metabolism [18]. In the case of Cu deficiency, these processes are impaired, leading to a reduction in Hb levels and disturbance in Fe metabolism.…”
Section: Mineral Contents In the Blood And Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Research in both animals and humans has demonstrated a significant correlation between Cu deprivation and anemia. Cu plays a crucial role in the body, particularly in the formation of red blood cells, as it is a cofactor for enzymes involved in hemoglobin synthesis and Fe metabolism [18]. In the case of Cu deficiency, these processes are impaired, leading to a reduction in Hb levels and disturbance in Fe metabolism.…”
Section: Mineral Contents In the Blood And Livermentioning
confidence: 99%
“…Similarly, when animals consume Se-rich plants, it usually accumulates in the form of selenate or Se-methylselenocysteine, resulting in acute selenosis and eventual death of livestock [17]. Long-term survival in a Se-rich environment can result in chronic selenosis in the Przewalski's gazelle, which is marked by anemia, impaired antioxidant function, poor immunological function, and aberrant phenylalanine metabolism [18].…”
Section: Introductionmentioning
confidence: 99%